Meta-Analysis of Randomized Controlled Trials on the Efficacy and Safety of Donepezil, Galantamine, Rivastigmine, and Memantine for the Treatment of Alzheimer’s Disease - Li, Dan-Dan; Zhang, Ya-Hong; Zhang, Wei; Zhao, Pu (Frontiers in Neuroscience, 2019)
To study the impact of donepezil, rivastigmine, galantamine, and memantine on cognitive, functional, behavioral, global changes and adverse effects in patients with mild, moderate and severe Alzheimer’s disease (AD), we screened the literature published before September 2017 in the Pubmed, Embase, Cochrane library and Web of Science Electronic databases according to the inclusion criteria. Thirty-six studies were finally determined from 1560 preliminary screened articles. The AD Assessment Scale-cognitive Subscale (ADAS-cog), AD Cooperative Study-Activities of Daily Living (ADCS-ADL), Neuropsychiatric Inventory (NPI), and Clinician’s Interview-Based Impression of Change Plus Caregiver Input scale (CIBIC+) were used as valid endpoints. Of the 36 trials included, meta-analyses of these placebo-control trials showed that there were significant differences between the donepezil, rivastigmine and placebo groups using ADAS-cog, ADCS-ADL, and CIBIC+. Meta-analyses of these placebo-controlled trials showed that there were significant differences between the galantamine and placebo groups using ADAS-cog, ADCS-ADL, NPI, and CIBIC+. These observations suggest that memantine is beneficial for stabilizing or slowing the decline in ADAS-cog and ADCS-ADL19 changes in AD patients. However, there was no significant effect according to the ADCS-ADL23, NPI, and CIBIC+ tests, which indicated that memantine treatment has no significant effect on these cognitive aspects of AD patients. Different effects of donepezil, rivastigmine, galantamine, or memantine on AD were found in this study. According to the results, we conclude that galantamine is effective in treating all aspects of AD and is the first choice for the treatment of AD. However, due to limited data, we should consider additional data to obtain more stable results.